NUMERICAL INVESTIGATION OF ADATOM-ADATOM INTERACTION EFFECTS ON SURFACE DIFFUSION DYNAMICS IN TWO-DIMENSIONAL MATERIALS - Rehab N. Hasnawi; Fatima H. Saeed (International Journal Multidisciplinary (IJMI), 2026)
Objective: Adatom dynamics on the surfaces of two-dimensional (2D) materials is important for catalysis, nanoscale depositions, and electronic or optoelectronic applications. In this paper, we present a numerical treatment of the two-dimensional nonlinear diffusion equation dependent on the coverage function (q) subject to Neumann boundary. Method: The adopted solution strategy is a hybrid of three techniques. The implicit Euler method is first used to discretize the time derivative leading to a second - order nonlinear partial variables. Secondly, the two dimensional is completely discretized by using second-order central difference approximations in time-finite different method giving non-linear algebraic equation. At last, an approximate solution are obtained iteratively by using Newton method. Results:We show that adatom- adatom interactions are essential for governing surface diffusion behavior on two-dimensional, thus providing guidance for nanomaterial design and potentially nanoelectronic device engineering. Novelty: The adopted solution strategy is a hybrid of three techniques.